Acute Disseminated Encephalomyelitis Presenting with Neuropsychiatric Symptoms - Mrinal Shrestha; Anish Joshi; Ajit Pandey; Aashutosh Chaudhary; Aman Raj Shrestha; Naman Koju; Sujan Timilsina; Ashlesha Chaudhary (Hindawi Limited, 2024)
Background. Acute disseminated encephalomyelitis (ADEM) is a rare immune-mediated pathology involving inflammatory demyelination of the central nervous system. Case Presentation. In this case report, we present the case of a nine-year-old female who exhibited altered mental status and focal neurological deficit, subsequently diagnosed as ADEM based on clinical presentation and magnetic resonance imaging (MRI) findings. The patient was managed symptomatically along with glucocorticoids. Conclusion. ADEM must be suspected when a patient, especially a child, presents with prodromal symptoms followed by multifocal neurological symptoms. Diagnosis can be established with an MRI brain scan. Most patients respond to high-dose intravenous glucocorticoids.